2021
DOI: 10.1111/acel.13317
|View full text |Cite
|
Sign up to set email alerts
|

Metformin inhibits chronic kidney disease‐induced DNA damage and senescence of mesenchymal stem cells

Abstract: Mesenchymal stem cells (MSCs) are promising source of cell‐based regenerative therapy. In consideration of the risk of allosensitization, autologous MSC‐based therapy is preferred over allogenic transplantation in patients with chronic kidney disease (CKD). However, it remains uncertain whether adequate cell functionality is maintained under uremic conditions. As chronic inflammation and oxidative stress in CKD may lead to the accumulation of senescent cells, we investigated cellular senescence of CKD MSCs and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 45 publications
1
36
0
Order By: Relevance
“…Metformin, a widely used miracle drug, is well known for treating type 2 diabetes. However, with advances in epidemiological and experimental researches, growing evidence suggests that metformin has multiple benefits in various diseases, including fibrotic diseases [ 55 57 ]. For example, metformin was found to alter the fate of myofibroblasts by inducing lipogenic differentiation and inhibit TGF-β1-stimulated myogenic differentiation [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…Metformin, a widely used miracle drug, is well known for treating type 2 diabetes. However, with advances in epidemiological and experimental researches, growing evidence suggests that metformin has multiple benefits in various diseases, including fibrotic diseases [ 55 57 ]. For example, metformin was found to alter the fate of myofibroblasts by inducing lipogenic differentiation and inhibit TGF-β1-stimulated myogenic differentiation [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…There are several findings that demonstrate the consequences of metformin treatment on MSCs biology. In a mouse model of kidney disease, a short pulse of metformin inhibited the acute senescence of bone marrow MSCs (Kim et al, 2021). Others have shown that metformin reduces the level of ROS and the onset of senescence in mouse adipose-derived MSCs (Marycz et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies evaluated the effects of metformin on MSCs biology. Metformin treatment protects MSCs from DNA damage events, delays senescence, reduces their level of reactive oxygen species, and promotes differentiation phenomena (Gu et al, 2017;Kuang et al, 2020;Kim et al, 2021). Additionally, metformin may enhance the immunomodulatory potential of MSCs (Park et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Metformin, a widely used miracle drug, is well known for treating type 2 diabetes. However, with advances in epidemiological and experimental researches, growing evidence suggests that metformin has multiple bene ts in various diseases, including brotic diseases [43][44][45]. For example, metformin was found to alter the fate of myo broblasts by inducing lipogenic differentiation and inhibit TGF-β1-stimulated myogenic differentiation [46].…”
Section: Discussionmentioning
confidence: 99%